Determinants of Solvency and Performance in Insurance: Role of Risk-Based Capital in Stability - Kevin Rafif; Noer Azam Achsani; Laily Dwi Arsyanti; Abylay Syzdykov (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The insurance sector's solvency and performance are critical for financial stability, particularly under the influence of Risk-Based Capital (RBC) regulations. These regulations enhance industry resilience, mitigating financial instability risks.Purpose: This study aims to identify the determinants of solvency and performance within the insurance industry, emphasizing the role of RBC regulations.Methodology: A systematic literature review of 20 empirical studies, published from 2018 to 2024, was conducted. Studies were selected based on relevance to solvency and performance and analyzed for regional and economic trends.Findings: Profitability, company size, and leverage were identified as significant internal factors influencing solvency. Specifically, profitability positively impacts solvency, while high leverage heightens vulnerability during economic downturns. RBC regulations contribute to industry stability but may restrict insurers’ capacity for higher-yield investments, thereby affecting profitability.Conclusion: Effective solvency management requires balanced regulatory strategies. RBC regulations support financial stability but must be crafted to allow growth, enabling insurers to manage risks while pursuing profitability.State of the art: This research provides insights into RBC regulation effects on the insurance sector's financial health, offering policy recommendations to promote stability and growth. Keywords: solvency, risk-based capital, insurance sector, profitability, regulatory frameworks